As interfaces da língua portuguesa frente às práticas pedagógicas: narrativa de uma professora no programa Um Gestar em Cada Escola - Mascarenhas, Ana Sheila Soares (2013)
This study is a reflective narrative of my experiences from training and professional work as a teacher of English in public schools in Feira de Santana, Bahia, with focus and focus on Program A gestate in each school (Learning Management school - gestate). Under a critical bias, analyzing the importance of Community Education, Religious Education, teaching practice and knowledge needed for teaching language from the perspective of being a teacher and his relationship with the construction of a professional identity and its dimension. This work aims to reflect the importance of training and upgrading of teachers, as well as highlight the proactive stance of a teacher researcher emphasized by researcher Stella Maris Bortoni-Ricardo, seeking a praxis that involves skill, knowledge of new technologies, respect, creativity , critical analysis, teamwork and autonomy.